The foci of in-action professional judgement and decision-making in high-level adventure sports coaching practice. Issue 2 (3rd April 2017) - Collins, Loel; Collins, Dave
ABSTRACT: This article continues a theme of previous investigations by the authors and examines the focus of in-action reflection as a component of professional judgement and decision-making (PJDM) processes in high-level adventure sports coaching. We utilised a thematic analysis approach to investigate the decision-making practices of a sample of high-level adventure sports coaches over a series of sessions. It was discovered that adventure sports coaches utilise a combination of questioning and observation to collect and constantly verify the information that forms the basis of their PJDM. Each coach responds to matters of immediate security, collecting information until a best-fit decision can be made regarding changes to the environment, task or individual. Implications for professional training, accreditation and development are presented against these data, offering a template for a more expertise-focused progression in the adventure sports coaching profession.